An indigenous South African perspective on workplace bullying - Mabasa, Fumani Donald (My University, 2021)
Workplace bullying is a complex and widespread phenomenon, which has become a challenge to understand as an organisational phenomenon because of its complexity and numerous labels and terms that are used interchangeably by researchers, media and the public, when describing the behaviour. The potential for bullying in the workplace is always present in situations where people continually interact. Currently, workplace bullying has become a phenomenon that has caused significant problems when ignored. This study endeavoured to explore workplace bullying from African indigenous perspective with no predominantly continuation of the work from Western countries and develop strategies and model of managing workplace bullying from an African perspective. This empirical study was conducted in Limpopo province and grounded theory was used as methodological strategy with twenty-one indigenous research participants selected through the use of snowball sampling. Furthermore, the constructivist worldview formed the basis of the study on workplace bullying accounts, which was generated through semi-structured interviews with the support of interview guide. Interviews were recorded using call phone recorder, transcribed, coded and analysed using Microsoft Excel and interpreted. Thus, six key themes emerged from this study to address shared themes from individual accounts of workplace bullying incidents, causes and consequences from indigenous, contextualised perspective. The findings of the study identified nine accounts of bullying behaviour. These are disrespect, rumours or bad-mouthing, name calling, threats, unfair treatment, yelling to cause public humiliation, infringement of rights, work overload and domineering. Furthermore, contracts of employment and demonstration of power was identified as causes and dynamics of bullying behaviour. The findings also showed that workplace bullying accounts resulted in high turnover rate, compromised employee well-being and performance. Most participants managed workplace bullying by “doing nothing”. The data also showed that age and gender play a significant role in the African contexts, taking into consideration shared cultural believes and customs. The study further provided a practical model for managing workplace bullying from an African perspective. Furthermore, the study proposes a need for workplace bullying legislation to further increase the severity of bullying behaviour. The study also highlights a need to incorporate indigenous knowledge when managing workplace bullying. Keywords: Workplace bullying; Indigenous knowledge; Western knowledge; Consequences; Conceptual framework; Culture
Thesis (Ph.D. Commerce (Human Resource Management)) -- University of Limpopo, 2021
Keywords: Workplace bullying; Indigenous knowledge; Western knowledge; Consequences; Conceptual framework; Culture; Organisational -- Wellbeing; Violence in the workplace -- Prevention; Bullying in the workplace